Frequency of HLA DQβ1*0201 and DQβ1*0301 Alleles and Total Serum IgE in Patients with Bronchial Asthma: A Pilot Study from Pakistan - Bushra Mubarak; Nadeem Afzal; Khursheed Javaid; Rakhshanda Talib; Rabia Aslam; Waqas Latif; Saba Khaliq (Iranian Journal of Allergy, Asthma and Immunology, 2017)
In Pakistan about 3.7% of the population is suffering from asthma, a chronic inflammatory disorder of airways. Asthma has wide spectrum of predisposing factors including environment and genetics. Many studies have been performed to determine association of asthma with serum IgE and major histocompatibility complex (MHC) alleles but conflicting results were reported. Therefore, present study was designed to determine frequency of HLA-DQβ1*0201 and DQβ1*0301 alleles in patients with bronchial asthma. This case control study included 85 asthmatic patients and 85 healthy controls. HLA-DQβ1*0201 and DQβ1*0301 alleles were detected by allele specific PCR and serum IgE was determined by ELISA. Median and inter-quartile range (IQR) of total IgE level were more increased in asthma patients (585.7 IU/mL and 247.2-848.1 IU/mL) compared to healthy controls (65.1 IU/mL and 28.1-181.3 IU/mL) (p<0.001). Frequency of HLA-DQβ1*0201 and -DQβ1*0301 alleles was more in healthy controls (32% and 38%, p=0.616) as compared to bronchial asthma patients (28% and 26%, p= 0.09). There was a significant association of IgE levels and HLA-DQβ1*0201 allele. Patients positive for HLA-DQβ1*0201 allele had low level of serum IgE 357.2 IU/mL (153.9-634.3 IU/mL) compared to the patients negative for this HLA allele i.e. 642.9 IU/mL (289.8-1299.5IU/mL) (p=0.005), whereas, HLA-DQβ1*0301 allele was not associated with total serum IgE level (p=0.865). Our findings show that HLA-DQβ1*0201 and -DQβ1*0301 alleles were not associated with asthma; however, HLA-DQβ1*0201 allele was associated with low levels of total serum IgE in the study population.